KINERJA MUDHARABAH DITINJAU DARI RASIO CAMEL PADA BANK UMUM SYARIAH DI INDONESIA - Natalia, Kristin (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of CAMEL ratio to the mudharabah performance which is proxy by the mudharabah profit portion. The population in this research is Syariah commercial banks which are listed in Bank Indonesia (BI). In this research, the sample collection technique has been determined by using purposive sampling, and based on the criteria 3 Syariah commercial banks have been selected as samples. The research data is secondary data which is the quarterly financial report of Syariah commercial Banks which have been published by Bank Indonesia during the year of 2009 until 2012. The data analysis is performed by using multiple linear regressions and classic assumption test analysis technique. The result of research shows that the NPF variable has negative influence to the performance of mudharabah since good financing management will reduce high problematic financing. The ROA variable has positive influence to the mudharabah performance since the bank position is getting better in terms of the use of assets so it can generate profit. Meanwhile, CAR, GWM and FDR variables do not have any influence to the mudharabah performance.Keywords:Performance, Mudharabah Financing, CAMEL Ratio.